Characterization of Dendritic Cell-Derived Extracellular Vesicles During Dengue Virus Infection - Martins, Sharon de T.; Kuczera, Diogo; Lötvall, Jan; Bordignon, Juliano; Alves, Lysangela R. (Frontiers in Microbiology, 2018)
The dengue virus (DENV), transmitted by Aedes spp. mosquitoes, is one of the most important arboviral infections in the world. Dengue begins as a febrile condition, and in certain patients, it can evolve severe clinical outcomes, such as dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). The reasons why certain patients develop DHF or DSS have not been thoroughly elucidated to date, and both patient and viral factors have been implicated. Previous work has shown that a severe immune dysfunction involving dendritic cells and T cells plays a key role in increasing the disease severity, especially in secondary heterologous infections. Extracellular vesicles (EVs) are membranous particles that are secreted by several cell types involved in homeostatic and pathological processes. Secretion of EVs by infected cells can enhance immune responses or favor viral evasion. In this study, we compare the molecular content of EVs that are secreted by human primary dendritic cells under different conditions: uninfected or infected with DENV3 strains isolated from patients with different infection phenotypes (a severe case involving DSS and a mild case). Human monocyte-derived dendritic cells (mdDCs) were infected with the dengue virus strains DENV3 5532 (severe) or DENV3 290 (mild), and the EVs were isolated. The presence of cup-shaped EVs was confirmed by electron microscopy and immunostaining with CD9, CD81 and CD83. The RNA content from the mdDC-infected cells contained several mRNAs and miRNAs related to immune responses compared to the EVs from mock-infected mdDCs. A number of these RNAs were detected exclusively during infection with DENV3 290 or DENV3 5532. This result suggests that the differential immune modulation of mdDCs by dengue strains can be achieved through the EV pathway. Additionally, we observed an association of EVs with DENV-infectious particles that seem to be protected from antibodies targeting the DENV envelope protein. We also showed that EVs derived from cells treated with IFN alpha have a protective effect against DENV infection in other cells. These results suggested that during DENV infection, the EV pathway could be exploited to favor viral viability, although immune mechanisms to counteract viral infection can also involve DC-derived EVs.